Video y escritura. La inscripción en la interface electrónica y digital - Jacobo Sucari (Cuadernos LIRICO)
Changes in the technical device bring with them transformations in the forms they convey. The invention of the electronic image of video, and later of digital compression, opened the doors to radical experimentation that changed the clichés of the film industry and the roles occupied by filmmakers and writers. This article sets references from the point of view of a media archaeology on the processes of audiovisual construction that have modified, since the electronic revolution, the relationship between text and image.